Alternative feeding strategies and genetics for providing adequate methionine in organic poultry diets with limited use of synthetic amino acids. Issue 1 (1st March 2016) - Burley, H.K.; Patterson, P.H.; Anderson, K.E.
Abstract : Currently, synthetic methionine (Met) use in organic poultry diets in the United States is limited to 1, 1, and 1.5 kg per metric tonne of feed for laying hens, broilers, and turkeys and other poultry, respectively. This limitation, and the push to ban the use of synthetic Met entirely, makes it challenging to formulate diets to meet the requirements of these birds. Methionine levels can be maintained in organic poultry diets without synthetics by dramatic increases in dietary crude protein; however, the ramifications of such high crude protein intake are major increases in feed cost and environmental concerns due to increased nitrogen excretion, rises in ammonia emissions, and subsequent welfare issues. This review examines alternative bird genetics and feeding strategies that have the potential to reduce or eliminate the need for synthetic Met in organic poultry diets. Alterative 'heritage' breeds may have lower Met needs as a percentage of the total diet; however, these birds have substantially slower growth and are less productive compared to typical commercial breeds. Feeding strategies that have been examined to reduce Met inclusion in the diet, such as allowing birds to forage, providing low Met density diets to encourage increased feed intake and subsequently make up for the Met deficiency, allowing birds to self select between energy-rich ingredients and protein concentrates to meet their Met needs by instinct, or supplementing methyl donors (betaine or choline) or inorganic sulphate, have been shown to make up for marginal Met deficiencies in some instances. However, there is no one solution to this issue that has been found thus far. A combination of genetics, feeding strategies, and alternative ingredients may provide the most favourable solution in the future.